Perancangan Perangkat Modular Kendali Suhu dan Aliran Gas Elpiji Berbasis Fuzzy Logic - Harsawardana; Ulfah, Maria; Samodro, Bayu (Emitor: Jurnal Teknik Elektro, 2024)
AbstractTemperature is very significant in every stage in the heating processes and will affect the quality of the resulting product. The inaccuracy of temperature control causes the production process to change from time to time, in addition to the increasingly inconsistent quality of the resulting product. In this study, the use of a closed loop system based on fuzzy logic will be applied to control the temperature and flow of fuel. Temperature control is connected to gas flow control because this equipment is specifically for gas (LPG) fueled equipment. By the fuzzy logic system, it is expected to produce a control equipment that can control temperature accuratly and can save fuel. This control equipment is modular in nature so that it can be applied to all bakery & cake oven equipment, coffee roasters, tea leaf wiping machines, fryers and other small scale industrial machines without having to change and modify the original design. The temperature settling point can be adjusted from 80oC to 300oC as desired in the heating process. The test results show that temperature control using fuzzy logic control system on coffee roasters and bread ovens obtains a maximum overshoot value which is still within the tolerance of 1.3% and fuel savings of around 13%